How and why policy design matters: understanding the diverging effects of public-private partnerships in education. Issue 2 (2nd April 2020) - Verger, Antoni; Moschetti, Mauro C.; Fontdevila, Clara
ABSTRACT: Despite Public-Private Partnerships' (PPPs) growing popularity within education policy circles, research on their effects yields contradictory results. The understanding of PPP effects is limited by the prevalence of generalist analyses that neglect to acknowledge the exceptional heterogeneity of the policy frameworks in which PPPs crystallize. Building on a scoping literature review, this paper aims at identifying patterns of effects of main PPP modalities on education (namely vouchers, charter schools and public subsidies for private schools) by considering the mediating role of policy-design variables. Our results show that PPP configurations oriented at the generation of market-like dynamics are frequently found to exacerbate school segregation and educational inequalities. Conversely, those PPP arrangements less conducive to market competition and those that follow an affirmative action rationale (such as targeted vouchers) are more likely to yield more positive effects on learning outcomes than other types of PPPs, without necessarily undermining equity.